Nutritional assessment of hospitalized patients: agreement between different methods - Rafaella Maria Monteiro Sampaio; Francisco José Maia Pinto; Cláudia Machado Coelho Souza de Vasconcelos (Universidade de Fortaleza, 2012)
Objective: To evaluate the correlation between the nutritional diagnosis by subjective global nutritional assessment (SGA) and that obtained by anthropometric measurements in patients admitted to a public hospital in the city of Fortaleza-CE, Brazil. Methods: Assessment of nutritional status was conducted for all 50 patients who were hospitalized in the period from August to September 2008. Besides measurement of weight, height, arm circumference andtriceps skinfold thickness, SGA form was applied to each patient. Nutritional status was established based on the percentage of appropriateness of each measure and on the scores obtained through the form. Agreement between the diagnoses obtained by the two methodswas assessed using the chi-square test with continuity correction. Results: Study participants were 31 (62%) male patients and 19 (38%) females, aged 37.08 ± 11.92 years. Association was found between nutritional diagnosis through SGA and nutritional diagnosis based onfinal anthropometric evaluation, with statistically significant differences (p = 0.047) between both diagnoses. Conclusion: There may be disagreement concerning nutritional diagnosis when the patient is assessed by different methods.